Identifying Ultimate Controlling Shareholders In Indonesian Public Companies: an Empirical Survey - Sobirin, Achmad; Fahruddin, MZ.; Rosid, Andiana (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2019)
This paper aims to identify the ultimate ownership of public companies that are listed on the Indonesia Stock Exchange (IDX) during 2014-2017 period. Identification techniques used in this study are: (1) tracking the ownership structure; (2) measuring the level of control; (3) determining the majority ownership, and (4) finding the ‘controlling shareholder’ narrative in the annual report. Based on tim research analyze, this paper found that the ultimate ownership of public companies in Indonesia 2014-2017 was concentrated in the ultimate family owners (54.43%), corporations (31.05%) and the state (7.49%). Beside it, 89.43% of families use the indirect ownership structure (pyramid ownership). In addition, more than 50% of the ultimate family ownership place their family members in the Board of Commissioner (BOC) and Board of Directors (BOD).